A genome-wide association study identifies risk loci for spirometric measures among smokers of European and African ancestry. Issue 1 (December 2015) - Lutz, Sharon; Cho, Michael; Young, Kendra; Hersh, Craig; Castaldi, Peter; McDonald, Merry-Lynn; Regan, Elizabeth; Mattheisen, Manuel; DeMeo, Dawn; Parker, Margaret; Foreman, Marilyn; Make, Barry; et al.
Abstract Background Pulmonary function decline is a major contributor to morbidity and mortality among smokers. Post bronchodilator FEV1 and FEV1 /FVC ratio are considered the standard assessment of airflow obstruction. We performed a genome-wide association study (GWAS) in 9919 current and former smokers in the COPDGene study (6659 non-Hispanic Whites [NHW] and 3260 African Americans [AA]) to identify associations with spirometric measures (post-bronchodilator FEV1 and FEV1 /FVC). We also conducted meta-analysis of FEV1 and FEV1 /FVC GWAS in the COPDGene, ECLIPSE, and GenKOLS cohorts (totaln = 13, 532). Results Among NHW in the COPDGene cohort, both measures of pulmonary function were significantly associated with SNPs at the 15q25 locus [containingCHRNA3 /5, AGPHD1, IREB2, CHRNB4 ] (lowestp -value = 2.17 × 10−11 ), and FEV1 /FVC was associated with a genomic region on chromosome 4 [upstream ofHHIP ] (lowestp -value = 5.94 × 10−10 ); both regions have been previously associated with COPD. For the meta-analysis, in addition to confirming associations to the regions nearCHRNA3/5 andHHIP, genome-wide significant associations were identified for FEV1 on chromosome 1 [TGFB2 ] (p -value = 8.99 × 10−9 ), 9 [DBH ] (p -value = 9.69 × 10−9 ) and 19 [CYP2A6/7 ] (p -value = 3.49 × 10−8 ) and for FEV1 /FVC on chromosome 1 [TGFB2 ] (p -value = 8.99 × 10−9 ), 4 [FAM13A ] (p -value = 3.88 × 10−12 ), 11 [MMP3/12 ] (p -value = 3.29 × 10−10 ) and 14 [RIN3 ] (p -value = 5.64 × 10−9 ). Conclusions In a large genome-wide association study of lung function in smokers, we found genome-wide significant associations at several previously described loci with lung function or COPD. We additionally identified a novel genome-wide significant locus with FEV1 on chromosome 9 [DBH ] in a meta-analysis of three study populations.